2017
DOI: 10.3389/fcvm.2017.00060
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: New Players in the Pathobiology of Preeclampsia

Abstract: Our understanding of how microRNAs (miRNAs) regulate gene networks and affect different molecular pathways leading to various human pathologies has significantly improved over the years. In contrary, the role of miRNAs in pregnancy-related hypertensive disorders such as preeclampsia (PE) is only beginning to emerge. Recent papers highlight that adverse pregnancy outcomes are associated with aberrant expression of several miRNAs. Presently, efforts are underway to determine the biologic function of these placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 79 publications
(83 reference statements)
0
82
0
5
Order By: Relevance
“…Growing evidence supports that PE results from abnormal placental development and function, however, the pathophysiological mechanisms of PE remain poorly understood. In normal pregnancies, cytotrophoblasts (CTBs) migrate through the decidua and myometrium in order to invade the maternal spiral arteries of the endothelium and tunica media . Inadequate invasion possibly results in reduced uteroplacental perfusion pressure (RUPP) and placental ischaemia/hypoxia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence supports that PE results from abnormal placental development and function, however, the pathophysiological mechanisms of PE remain poorly understood. In normal pregnancies, cytotrophoblasts (CTBs) migrate through the decidua and myometrium in order to invade the maternal spiral arteries of the endothelium and tunica media . Inadequate invasion possibly results in reduced uteroplacental perfusion pressure (RUPP) and placental ischaemia/hypoxia .…”
Section: Introductionmentioning
confidence: 99%
“…In normal pregnancies, cytotrophoblasts (CTBs) migrate through the decidua and myometrium in order to invade the maternal spiral arteries of the endothelium and tunica media. 5 Inadequate invasion possibly results in reduced uteroplacental perfusion pressure (RUPP) and placental ischaemia/hypoxia. 6 Ischaemia-induced oxidative stress also leads to the apoptosis and necrosis of the placenta as well as the release of several placental factors, resulting in endothelial dysfunction, and systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The elveation of miR‐210 in the uteroplacental tissues has been implicated in the pathogenesis of preeclampsia and IUGR (Bounds et al . ; Chiofalo et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate multiple fundamental cell processes and participate in the development and progression of various diseases . Of note, a growing body of evidence has suggested that miRNAs are crucial regulators in the pathology of PE . miRNAs are abundantly expressed in human placental tissues, and various miRNAs have been shown to be dysregulated in PE .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Of note, a growing body of evidence has suggested that miRNAs are crucial regulators in the pathology of PE. [8][9][10] miRNAs are abundantly expressed in human placental tissues, and various miRNAs have been shown to be dysregulated in PE. 11,12 These abnormally expressed miRNAs can be used as diagnostic markers for PE as well as therapeutic targets.…”
mentioning
confidence: 99%